1983
DOI: 10.1016/0024-3205(83)90382-x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired lymphocyte function in depressive illness

Abstract: Mood states and immunity may be related. To investigate the immune status of patients with primary depressive illness, we compared in-vitro lymphocytic responses to three different mitogens in 26 drug-free depressed patients and 20 normal controls of comparable age and sex. We observed a generalized and marked decrease in the lymphocyte mitogenic activity among the depressive group. This defect in lymphocyte function may be indicative of an impairment in cell-mediated immunity in patients with primary depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
3

Year Published

1985
1985
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(78 citation statements)
references
References 15 publications
4
70
1
3
Order By: Relevance
“…The higher DPM following PWM stimulation in depressed patients did not reach even trend level. Our results differ from several observations reporting a clear-cut attenuated mitogen response following administration of various lectins in depressed patients (Kronfol et al 1983;Schleifer et al 1984;Cosyns et al 1989). However, the mitogen-induced blastogenesis has recently been attributed more to factors such as age, severity of depression, and hospitalization effects than to the diagnosis itself (Schleifer et al 1989).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The higher DPM following PWM stimulation in depressed patients did not reach even trend level. Our results differ from several observations reporting a clear-cut attenuated mitogen response following administration of various lectins in depressed patients (Kronfol et al 1983;Schleifer et al 1984;Cosyns et al 1989). However, the mitogen-induced blastogenesis has recently been attributed more to factors such as age, severity of depression, and hospitalization effects than to the diagnosis itself (Schleifer et al 1989).…”
Section: Discussioncontrasting
confidence: 99%
“…A variety of studies have investigated lymphocyte subsets (Schleifer et al 1989), natural killer cell activity (Irwin et al 1988;Schleifer et al 1989), and the mitogen response to various lectins (Kronfol et al 1983;Schleifer et al 1984Schleifer et al , 1985Cosyns et al 1989). Although initial studies reported a decreased mitogen-induced leucocyte proliferation in depressed patients (Kronfol et al 1983;Schleifer et al 1984), this could not be consistently reproduced in later investigations (Schleifer et al 1985). Instead, other variables, such as age and severity of depression, seemed to play a key role for the lectin-induced blastogenesis (Schleifer et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the studies reported in the five years prior to the 1989 report by Schleifer et al were based on small samples, the majority found significant decreases in mitogen-stimulated lymphocyte responses in unmedicated depressed patients as compared with control subjects (Kronfol et al 1983(Kronfol et al , 1986Schleifer et al 1984;Syvalahti et al 1985;Calabrese et al 1986;Darko et al 1988). Differences have been more distinct in studies of older patients and those hospitalized for more severe depressive disorders, suggesting either that age and/or severity of depression are independent determinants of impaired immunity or that a higher-order CNS disturbance is a cause of both the endogenous sub-type and immune dysfunction.…”
Section: Immune Dysfunction In Depressive Disordermentioning
confidence: 96%
“…211 Dysregulated activity of the immune system in depression, with increased proinflammatory activity, has repeatedly been demonstrated. [212][213][214][215][216] In addition, inflammatory diseases are typically associated with depressed mood. 217,218 Administration of proinflammatory cytokines (e.g.…”
Section: Stressmentioning
confidence: 99%